Bung Hatta dan Politik Bebas Aktif Indonesia - Malikul Kusno (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2014)
Bung Hatta, one of Indonesian founding fathers, has had very briliant vision for Indonesian foreign policy following our independence August 17, 1945. Since the end of colonial era, his principle to implement “politik bebas aktif” (free and active politics) in international arena has been underpinning for Indonesia foreign policy, both in the era of Cold War in what the so-called “sailing between two reefs namley Communist Bloc and Capitalist one” and in the aftermath. Hatta’s vision is still relevant for us in implementing Indonesian’s foreign policy in the era of globalized world today, in which the fall of communism and the winning of capitalism has been the challenges for the developing countries such as the Non-Alignment movement and The Third World countries in doing their foreign policy for global peace, justice and security. The World is changing, but Hatta’s principle for Indonesian foreign policy is still contextual for our age.